Analisis Laba Berdasarkan Metode Full Costing pada Usaha Madu Bapak Tejo Matal si Desa Melaya - Putra, I Gusti Ngurah Pradnyana; Dewi, Luh Gede Kusuma (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
production based on the full costing method and how the profit earned on the honey business owned by Mr. Tejo Matal. In this study using qualitative methods. The data used in this study are primary data and secondary data. Data collection methods in the form of interviews, observations, and documentation. The results of this study state that the calculation of the cost of production according to Mr. Tejo Metal's calculations does not include fixed overhead costs and variable overhead costs. Then the cost of production obtained each bottle is Rp. 160,000 while according to the full costing method by calculating all costs, the result is Rp. 231,412. With a selling price of Rp. 200,000 profit according to Mr. Tejo Matal's calculation is in the figure of 25% or 40,000, while according to the full costing method the profit obtained is only around 7.4% or Rp. 14,870.